O sujeito-autor em discursos testamentais - Rocha, Anderson Jacob (2019)
The objective of this dissertation is to examine testament discourses materialized linguistically in Passos - MG, in the nineteenth century, in order to observe the authorship conditions of an enunciating subject who owns an individual discursive condition, preserving in his/her statements, the regularities enunciated by social institutions, marked in those discourses of juridical-religious constitution. In order to understand the discursive aspects revealing the circumstances of collective memories of the nineteenth century, it was necessary to know the kind of subject was participating of the testament discourse, whose authorship was revealed through statements recognized by categories of social-historical production conditions, inter-discourses, scenography, and discursive ethos. To achieve this, the French discourse analysis was chosen, principally the perspectives proposed by Dominique Maingueneau (1990; 1997a; 1997b; 2004; 2005; 2007; 2008a; 2008b; 2010a; 2010b; 2013; 2015), as a discipline able to provide us with basis to perform the revealing analyses of statements of people and places in the nineteenth century and understand social-psychic-religious matters, which, still, echo in current times